1969
DOI: 10.1115/1.3554901
|View full text |Cite
|
Sign up to set email alerts
|

Mean Free Path Effect in Spiral-Grooved Thrust Bearings

Abstract: The objective of this paper is to study the effect of molecular mean free path on the steady-state performance characteristics of a spiral-grooved thrust bearing operating in extremely thin film and/or low ambient pressure environments. Numerical results for the most popular three versions of the spiral-grooved designs are presented. These results reveal that the effect of slip boundary conditions could contribute substantial reduction, in performance. Helium is the worst gas lubricant in this sense because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Their results suggested that the local incompressibility effect overestimated the pressure rise within the fluid film due to both the compressibility and the rarefaction effects. Comparison with experimental data showed that their model performed better than the classical NGT model such as applied by Hsing and Malanoski [119].…”
Section: λ = −mentioning
confidence: 93%
See 2 more Smart Citations
“…Their results suggested that the local incompressibility effect overestimated the pressure rise within the fluid film due to both the compressibility and the rarefaction effects. Comparison with experimental data showed that their model performed better than the classical NGT model such as applied by Hsing and Malanoski [119].…”
Section: λ = −mentioning
confidence: 93%
“…The effect scales with the mean free molecular path. If the ratio between the clearance and the molecular mean free path drops below a threshold value, rarefaction effects start manifesting [1,119,136,137] resulting in a departure from the zero-velocity flow condition at the boundaries. The Knudsen number Kn, defined as the ratio between the molecular mean free path and the fluid film thickness, indicates the severity of rarefaction effect.…”
Section: Rarefaction Effects and Slip-flow Boundariesmentioning
confidence: 99%
See 1 more Smart Citation